20 Years of the German Euro Are More than Enough - Bibow , Jörg (Revista de Economía Crítica, 2024)
This paper reviews the performance of the euro area since the euro’s launch 20 years ago. It argues that the euro crisis has exposed existential flaws in the euro regime. Intra-area divergences and the corresponding buildup of imbalances had remained unchecked prior to the crisis. As those imbalances eventually imploded, member states were found to be extremely vulnerable to systemic banking problems and abruptly deteriorating public finances. Debt legacies and high unemployment continue to plague euro crisis countries. Its huge current account surplus highlights that the euro currency union, toiling under the German euro and trying to emulate the German model, has become very vulnerable to global developments. The euro regime is flawed and dysfunctional. Europe has to overcome the German euro. Three reforms are essential to turn the euro into a viable European currency. First, divergences in competitiveness positions must be prevented in future. Second, market integration must go hand in hand with policy integration. Third, the euro is lacking a safe footing for as long as the ECB is missing a federal treasury partner. Therefore, establishing the vital treasury–central bank axis that stands at the center of power in sovereign states is essential.